Answer:
The values in the table, taking into account the quadratic equation, are:
- x -3 -2 -1 0 1 2 3 4
- y 16 9 4 1 0 1 4 9
Explanation:
To obtain the values of the table, you must use the quadratic equation given:
Now, you must replace the x with the one that is above the value you want to find, in the first case, we're gonna replace the value x with -3:
- y = x^2 - 2x + 1
- y = (-3)^2 - 2*(-3) + 1
- y = 9 + 6 + 1
- y = 16
When x is -1
- y = x^2 - 2x + 1
- y = (-1)^2 - 2*(-1) + 1
- y = 1 + 2 + 1
- y = 4
When x is 1
- y = x^2 - 2x + 1
- y = (1)^2 - 2*(1) + 1
- y = 1 - 2 + 1
- y = 0
When x is 3:
- y = x^2 - 2x + 1
- y = (3)^2 - 2*(3) + 1
- y = 9 - 6 + 1
- y = 4
At last, the graph must be as the attached picture I give you, but remember in y-axis you must use 1 cm as unit and in the x-axis you must use 2 cm as unit, in this form, the graph will not be so elongated as the picture I attach, It would be wider.